Between Text and Terrain: 7th-Century Meccan Residential Structures - Tuncer, Faruk (South Asian Journal of Religion and Philosophy (SAJRP), 2025)
The houses of 7th-century Mecca have not been a subject of significant scholarly research. In fact, not only the houses of Mecca but also studies examining Mecca as a city with an urban identity are notably absent. Mecca has primarily been studied for its sacred status as the site of the Kaaba, a revered place of worship. While analyzing Mecca in terms of its sacred spaces is not inherently a deficiency, the focus of this study is to set aside Mecca's sanctity and investigate whether its houses, as part of an urban identity, hold any architectural significance or value. As far as can be observed, during the era in which the Prophet Muhammad lived and the Qur'an was revealed, the general appearance of Meccan houses did not represent an advanced level for its time. Based on the limited information available about the appearance of these houses, it isn't easy to provide a definitive depiction. However, an informed conjecture can be made. Accordingly, if the Kaaba and other sacred spaces in Mecca are excluded, it could even be questioned whether the area qualifies as a city. In this article, we have set aside Mecca's sanctity and examined the city not in all its aspects but solely in the context of its houses.